Laser Diode Radiation Phase Non-Uniformity Influence Account for Improvement Phototachymeter Accuracy Characteristics - Bialiauski, U. S.; Manak, I. S. (Elektronika ir Elektrotechnika, 2006)
The mathematical model of the phase range finder is elaborated, allowing to investigate a space-time structure of radiation in a dis-tant zone at phase variations of modulation in a near zone of the laser diode. The method is offered to decrease error of distances meas-urement by the phase phototachymeter, connected with a phase variation of modulation of the laser diode. Ill. 3, bibl. 2 (in English; summaries in English, Russian and Lithuanian).